Decolonising health sciences : reflections on innovation, epistemic justice, and advancing medical laboratory education in Africa - Thembane, Nokukhanya (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Medical Laboratory Science (MLS) education in Africa continues to reflect colonial legacies, with curricula and pedagogies largely shaped by Eurocentric frameworks that often overlook local health realities. This paper adopts a reflective, critical-interpretive methodology to explore the persistence of such frameworks and the ways in which they marginalise Indigenous knowledge systems while constraining innovation in health sciences training. Grounded in decolonial theory and the concept of epistemic justice, the analysis draws on interdisciplinary scholarship to investigate the epistemological assumptions rooted in MLS education. The paper argues that meaningful transformation requires dismantling inherited structures that privilege Western epistemologies over African ways of knowing and reimagining the curriculum as a site of both critique and possibility. In line with this objective, the paper proposes context-responsive pathways for reform, including curriculum redesign, inclusive teaching practices, and shifts in policy orientation aimed at promoting more equitable and locally relevant knowledge production. By foregrounding and centering African epistemologies and promoting critical reflexivity, the study positions health sciences institutions as key actors in advancing intellectual diversity and local expertise. This study contributes to ongoing conversations about curriculum transformation, offering a decolonial lens through which to rethink the future of MLS education in Africa.
Keywords: Science education; Medical laboratory; Indigenous knowledge systems; Epistemic justice; Decolonial Theory; Curriculum innovation; African health education; Ethnoscience; Medical personnel; Medical laboratory technology; Science -- Study and teaching